The effect of nutritional assistance “gammarana program” on food acceptance and nutritional status of children in South Sulawesi, Indonesia - Nadimin, Nadimin; Sirajuddin, Sirajuddin; Afifah, Sella Nur; Hadju, Veny; Bohari, Bohari (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: Nutritional deficiencies are a public health issue requiring serious attention in Indonesia. This study evaluates the impact of the Gammarana Program on infant and child feeding practices and nutritional status in South Sulawesi. The program includes nutritional education and counseling provided by Village Nutrition Assistants (TPGD) in stunting-prone villages. The study aimed to assess the program’s effectiveness in improving feeding frequency, dietary diversity, food acceptance, and overall nutritional status of children. Methods: A pretest-posttest design without a control group was used, involving 114 stunting-prone villages and 2,148 families. Over six months, TPGD provided education and counseling on infant and child feeding, growth monitoring, and supplementary feeding. Data were collected through interviews and anthropometric measurements and analyzed using McNemar’s test to determine changes before and after the intervention, with significance set at p<0.05. Results: Results showed a 12.1% increase in feeding frequency, a 27.1% increase in dietary diversity, and a 25.3% improvement in food acceptance. The proportion of underweight children decreased by 1.2%, stunted children by 5.4%, and underweight children by 2.6%. Significant improvements were observed in feeding frequency, dietary diversity, and stunting reduction. Additionally, the increase in average nutritional Z-scores indicated an overall improvement in children’s nutritional status. Conclusion: The Gammarana Program effectively improved feeding practices and reduced stunting rates in South Sulawesi.